Current Opera Production in the Repertoire of the Slovak National Theatre in 1960s - Mojžišová Michaela (Slovenské divadlo)
The study deals with the increase in the introduction of modern opera production at the Slovak National Theatre in the 1960s. The author interprets it not only as an attempt of dramaturgy to enliven the traditional repertoire, but in particular as an ambition to apply more modern theatrical poetics in the production opera practice. Since there was no practice of updating classic opera production in Slovakia in the sense of “Regietheater” at that time, this production of the 20th century was considered to be the most realistic way of reviving opera. At the same time, the study highlights the social motivation of this intention: an effort to address a new, progressively oriented audience that would create appeal for a conventionally oriented audience that primarily focuses on the musical-vocal component of opera productions.